Effect of increased dietary fiber on hoof lesions of loose housed sows - SKAMPARDONIS (Β. ΣΚΑΜΠΑΡΔΩΝΗΣ), V.; LISGARA (Μ. ΛΙΣΓΑΡΑ), M.; TZIKA (E. TZHKA), E. D.; LEONTIDES (Λ. ΛΕΟΝΤΙΔΗΣ), L. (Journal of the Hellenic Veterinary Medical Society, 2018)
Loose dry sow housing became mandatory in the European Union from January 2013 onwards. One of the major causes of injuries to sows’ hooves and associated lameness is fighting on concrete/slatted flooring at grouping. Previous studies observed that in sows submitted to feed restriction, feed supplemented with dietary fiber reduced the time spent in the standing position and increased the time spent in the lying position. Therefore, we investigated the effect of increased levels of dietary fiber (7.2-7.5% crude fiber/kg dry matter) on the severity of hoof lesions of group housed sows in three Greek swine herds. The feet of 596 sows were initially examined for lesions upon their entry to the lactation facilities. Lesions scored included hoof hyperkeratinization, erosions or cracks and toe and dew claws overgrowths. When exiting the farrowing facilities they were offered recipes with increased dietary fiber throughout one or two subsequent gestations. Thirty-eight percent were re-examined for feet lesions during the first and sixty-two percent during the second lactation after initial examination. The proportion of sows with at least one lesion on any foot, at first scoring, was more than 95% in all herds. The most frequently and severely affected sites were the heel and the elongated toes and dew claws. The increased dietary fiber had no effect on lesion severity on any of the hoof sites considered.